Investment in Human Resources to Increase Achievement Levels of Sustainable Development - Erlyn, Putri; Hidayat, Bachtari; Cahyo, Aji; Saksono, Herie (Jurnal Bina Praja, 2022)
The quality of life of a country or region describes the welfare of the people and the success of programs made by the government to improve the degree of human life. Life expectancy is one of the indicators used to assess the population's health status that describes the quality of life. In contrast, education is the basis for poverty alleviation and economic growth. Education and health are fundamental to building wider human capacities and are at the core of the meaning of development. This research was conducted to test the effect of poverty and education on public health in the city of Palembang. Secondary data sourced from the Central Statistics Agency in 2010-2019 were analyzed using multiple regression with Eviews 9 analysis software. The dependent variable is Life Expectancy as a proxy for public health rates. The independent variable is the average length of schooling as a proxy indicator of education and the number of poor people. This study shows that poverty is negatively correlated with public health. In contrast, the direction of education is negative, so it can be concluded that education has no significant effect on public health Poverty and education are factors that determine the level of public health in the city of Palembang, where the higher the education and the decrease in poverty, the higher the public health. In order to approach better public health status in Palembang City, poverty is reduced by reducing unemployment and increasing education through skills training.